Using Quiz Whizzer as a Medium for Evaluating Arabic Vocabulary Learning in Class VII.9 Students - Al Ghifary , Afif; Beddu Malla , Agussalim; Wahyudin, Wahyudin; Zainal , Abdul Qahar; Muhammad, Muhammad (Journal of Digital Arabic Language Education, 2025)
This study aims to describe the implementation of QuizWhizzer as an interactive medium for evaluating Arabic vocabulary learning and to examine students’ responses to its use in Grade VII.9 at MTsN 2 Makassar. The study was motivated by the low level of students’ interest and engagement resulting from the continued use of conventional evaluation methods. Therefore, a technology-based evaluation medium was needed to create a more interactive and enjoyable learning environment. This research employed a descriptive qualitative approach involving six Grade VII.9 students of MTsN 2 Makassar as research participants. Data were collected through classroom observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman data analysis model, which includes data reduction, data display, and conclusion drawing. The findings indicate that the use of QuizWhizzer creates a more enjoyable evaluation atmosphere, enhances students’ active participation, and increases learning motivation. Students reported feeling more relaxed and interested due to the game-based features and real-time feedback, which helped them identify errors more quickly. However, limitations related to device availability and internet connectivity were identified. Overall, QuizWhizzer is effective as an interactive evaluation medium for Arabic vocabulary learning at the junior secondary school level.